REPORT ON THE OCCURRENCE OF ONE SUBSPECIES OF SCYLLA SERRATA ( FOR SKAL) IN COCHIN BACK WATERS. - RADHAKRISHNAN, C K; SAMUEL, C T (Fishery Technology, 2017)
The taxonomy of the mud crab, Scy!!a serrata has become a topic of interest. Alcock (1899) described this species from Indian waters. It was considered that under the genus Scylla, only one- species, namely, Scylla serrata was valid. But Estampador (1949) revised the genus and reported the occurrence of four sorts, Scylla serrata, S. tranquebarica, S. oceanica and a variety S. serrata, var paramarnosain in Philippine waters. He established his claim based on the morphology such as colouration, relative length of chelae and also on the cytological events during gametogenesis. Serene (1952) pointed out that two distinct categories under this genus was demonstrable on the basis of colouration. But Stephenson & Campbell (1960) concluded them as only synonyms, but pointed out the need for further investigations.